Nurturing Islamic Values in Early Childhood in Thailand's Muslim Minority - Muzakki, Muzakki; Khatimah, Husnul; Saudah, Saudah; Aghnaita, Aghnaita; Mahama, Salmee (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Islam is the major religion in southern Thailand. However, it remains a minority religion compared to the overall Thai population. The Muslim community in Thailand places great importance on Islamic religious education. They teach about Islam to children from an early age to nurture and foster Islamic values. Besides, it's helping them to understand Islam as part of their identity in the country's diversity. This study aimed to describe the teaching of Islamic values in early childhood within Thailand's Muslim minority. The research method used descriptive qualitative. Data Collection was carried out through observation, interviews, and documentation. The research was conducted in a non-formal education, the Miracle Language Center in Mueng, Narathiwat, Thailand, held in August-September 2023. The subjects were ustadz and ustadzah (Islamic teachers) and early childhood students attending the center. The data analysis technique used data condensation, data presentation, and verification and conclusion drawing. The results showed that children were taught through various academic and religious activities. Academically, Arabic vocabulary was introduced through pictures and songs. Religiously, the focus was on faith, worship, and moral values. The faith was taught through the pillars of faith, Islam, and exemplary stories. Worship was taught through memorizing short surahs, daily prayers, and practicing prayer and ablution. Moral values were taught through lessons on civility and manners. This study serves as a reference for teaching Islamic values to young children in Muslim minority communities.